Prognostic Role of RASSF1A, SOX17 and Wif-1 Promoter Methylation Status in Cell-Free DNA of Advanced Gastric Cancer Patients. (30th April 2021) - Karamitrousis, Evangelos I.; Balgkouranidou, Ioanna; Xenidis, Nikolaos; Amarantidis, Kyriakos; Biziota, Eirini; Koukaki, Triantafyllia; Trypsianis, Grigorios; Karayiannakis, Anastasios; Bolanaki, Helen; Kolios, George; Lianidou, Evi; Kakolyris, Stylianos
Epigenetic modification of several genes is a key component in the development of gastric cancer. The methylation status of RASSF1A, SOX17 and Wif-1 genes was evaluated in the cell free circulating DNA of 70 patients with advanced gastric cancer, using methylation-specific PCR. Patients with higher cell-free DNA concentration seem to have lower PFS, than patients with lower cell-free DNA concentration (p = 0.001). RASSF1A was the tumor suppressor gene, most frequently methylated in metastatic gastric cancer patients, followed by SOX17 and Wif-1 (74.3%, 60.0% and 47.1%, respectively). Patients having the SOX17 promoter methylated, had lower progression free survival and overall survival, than unmethylated ones (p < 0.001). Patients having the Wif-1 promoter methylated, had lower progression free survival and overall survival, than unmethylated ones (p = 0.001). Patients having the RASSF1A promoter methylated, had lower progression free survival and overall survival, than unmethylated ones (p = 0.004). Promoter methylation of the examined genes was significantly associated with a decrease in progression free survival and overall survival, comparing to that of patients without methylation. Simultaneous methylation of the above genes was associated with even worse progression free survival and overall survival. The methylation of RASSF1A, SOX-17 and Wif-1 and genes, is a frequent epigenetic event in patients with advanced gastric cancer.